ANALISIS AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN DANA DESA DI DESA TOLALA KECAMATAN TOLALA KABUPATEN KOLAKA UTARA - Pirsya, Pirsya; Rijal, Abdul; Afiah, Nur (REMITTANCE: JURNAL AKUNTANSI KEUANGAN DAN PERBANKAN, 2024)
This research analyzes the accountability and transparency of village fund management in Tolala Village, Tolala District, North Kolaka Regency. The research variables are Accountability and Transparency in Village Fund Management, covering the stages of planning, implementation, administration, reporting, and accountability based on the Minister of Home Affairs Regulation Number 20 of 2018 concerning village fund management. The data analysis method in this study is descriptive qualitative. Data collection was conducted using documentation and interview techniques involving five respondents involved in village financial management, namely the Village Head, Village Secretary, Village Treasurer, Village Consultative Body (BPD), and the Community. The research results indicate that the accountability of village fund management in Tolala Village is quite good as it aligns with the Minister of Home Affairs Regulation Number 20 of 2018 concerning Village Fund Management, covering the stages of Planning, Implementation, Administration, and Accountability. However, the reporting stage is still not by the regulations. The principle of transparency in managing village funds in Tolala Village is already quite good by the Minister of Home Affairs Regulation.Penelitian ini bertujuan untuk menganalisis akuntabilitas dan transparansi pengelolaan dana desa pada Desa Tolala Kecamatan Tolala Kabupaten Kolaka Utara. Variabel penelitian adalah Akuntabilitas dan Transparansi Pengelolaan Dana Desa, dari tahap perencanaan, pelaksanaan, penatausahaan, pelaporan dan pertanggungjawaban berdasarkan Peraturan Menteri Dalam Negeri Nomor 20 Tahun 2018 tentang pengelolaan dana desa. Metode analisis data dalam penelitian ini adalah deskriptif kualitatitif. Pengumpulan data menggunakan teknik Dokumentasi dan Wawancara dengan melibatkan lima orang responden yang terlibat dalam pengelolaan keuangan desa yaitu Kepala Desa, Sekretaris Desa, Bendahara Desa, BPD, dan Masyarakat. Hasil penelitian menunjukan bahwa akuntabilitas pengelolaan dana desa di Desa Tolala sudah cukup baik karena sudah sesuai dengan Peraturan Menteri Dalam Negeri Nomor 20 Tahun 2018 tentang Pengelolaan Dana Desa mulai dari tahapan Perencanaan, Pelaksanaan, Penatausahaan dan Pertanggungjawaban. Sedangkan untuk tahap pelaporan masih belum sesuai. Untuk prinsip transparansi dalam pengelolaan dana desa di Desa Tolala juga sudah cukup baik sesuai Peraturan Menteri Dalam Negeri.